Sequestration of Hazardous Dyes from Aqueous Solution Using Raw and Modified Agricultural Waste - Mobolaji M. Jegede; Olatunde S. Durowoju; Joshua N. Edokpayi (Adsorption Science & Technology)
The continuous degradation of surface water quality by dye materials is of concern globally. Agricultural waste Litchi chinensis (LC) peel in its raw (RL) and modified (CL) forms was used as potential sorbents for sequestration of Congo red (CR) dye from an aqueous solution. The sorbents were characterized before and after sorption with Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), Brunauer, Emmett, and Teller (BET) surface area analysis, and X-ray diffraction (XRD). Determination of the point of zero charge (PZC) suggested CR dye sorption from an aqueous solution would be best in acidic pH. Batch experimental drivers such as the effects of time, dosage, initial concentration, pH, and temperature were optimized and used. Results from the study showed that modification with citric acid (CA) reduced the equilibration time from 90 to 15 min. Change in water chemistry did not significantly affect the removal efficiency of the sorbent but rather slightly improved it for both sorbent types. The smaller particle size of <125 μm recorded higher removal efficiency than the larger one (>125 μm). The effect of temperature affects the sorption differently. For the RL system, it decreases with an increase in the temperature, while for the CL system it increases with an increase in temperature. The Langmuir isotherm best described the equilibrium data obtained based on the linearized coefficients with maximum sorption capacities (qmax) of 55.56 mg/g (RL) and 58.48 mg/g (CL). The pseudo-second-order model also best described the kinetic data. The thermodynamics study showed that the reaction is both feasible and spontaneous. Both sorbents recorded high removal efficiency for other dyes such as rhodamine B, methylene blue, methyl orange, malachite green, and erythrosin B. The five cycled regeneration/sorption experiments with 0.1 M NaOH as the desorbing agent showed that the regenerated sorbents efficiently removed CR dye from an aqueous solution close to their virgin samples for the first three cycles. This research, therefore, establishes LC peel as a potential eco-friendly, readily available, and effective sorbent for sequestration of hazardous dyes from wastewater.